Simple Matrix Equation (SME) Method for Pattern Synthesis of Conformal Antenna Array with Arbitrary Architecture - Jie Chen (International Journal of Antennas and Propagation)
A novel noniterative method for pattern synthesis of conformal antenna array is put forward. First, a new pattern function formula for general conformal antenna array is derived. Then, according to the new pattern function formula, a new block matrix equation (BME) and a simple matrix equation (SME) are obtained. SME has the same form as the equation of linear array pattern synthesis. The new method can be applied to pattern synthesis of any conformal array. Moreover, due to SME having the same form as the matrix equation of linear array pattern synthesis, the new simple matrix equation can be dealt with by the approaches for linear array pattern synthesis, which significantly expands the existing approaches for conformal antenna array pattern synthesis. Two different conformal array configurations are taken as the examples to demonstrate the advantages of the new method. Results of the simulations show that the new method can flexibly and effectively be applied to synthesize patterns for various conformal array architectures.